Respostas

2014-04-23T17:52:11-03:00
a) x² - 1 = 0
Δ = 0² - 4 . 1 . (- 1)                X = - 0 +- √4  / 2 . 1
Δ = 0 + 4                              X = +- 2  / 2
Δ = 4
x' = 2  /  2 = 1                 x" = - 2  /  2 = - 1

b) x² - 4 x + 3 = 0
Δ = (- 4)² - 4 . 1 . 3                   X = - (- 4) +- √4  / 2 . 1
Δ = 16 - 12                              X = 4 +- 2  / 2
Δ = 4
x' = 4 + 2  / 2 => 6  / 2 = 3          x" = 4 - 2  / 2 => 2  / 2 = 1

c) x² + 3x + 2 = 0
Δ = 3² - 4 . 1 . 2                           X = - 3 +- √1  / 2 . 1 
Δ = 9 - 8                                      X = - 3 +- 1  / 2
Δ = 1
x' = - 3 + 1  / 2 => -2  / 2 = - 1            x" = - 3 - 1  / 2 => - 4  / 2 = - 2

d) x² + 4x + 3 = 0
Δ = 4² - 4 . 1 . 3                              X = - 4 +- √4  / 2 . 1
Δ = 16 - 12                                     X = - 4 +- 2  / 2
Δ = 4
x' = - 4 + 2  / 2 => - 2  / 2 = - 1               x" = - 4 - 2  / 2 => - 6  / 2 = - 3

e) x² + x - 2
Δ = 1² - 4 . 1 . (- 2)                          X = - 1 +- √9  / 2 . 1
Δ = 1 + 8                                        X = - 1 +- 3  / 2
Δ = 9
x' = - 1 + 3  / 2 => 2  / 2 = 1              x" = - 1 - 3  / 2 => - 4  / 2 = - 2

f) x² - x - 2
Δ = (- 1)² - 4 . 1 . (- 2)                       X = - (- 1) +- √9  / 2 . 1 
Δ = 1 + 8                                         X = 1 +- 3  / 2
Δ = 9
x' = 1 + 3  / 2 => 4  / 2 = 2                x" = 1 - 3  / 2 => - 2  / 2 = - 1

g) x² - 6x + 9
Δ = (- 6)² - 4 . 1 . (- 3)                         X = - (- 6) +- √0  / 2 . 1
Δ = 36 - 36                                        X = 6  / 2
Δ = 0                                                X = 3

h) x² - 2x - 3
Δ = (- 2)² - 4 . 1 . (- 3)                         X = - (- 2) +- √16  / 2 . 1
Δ = 4 + 12                                         X = 2 +- 4  / 2 
Δ = 16
x' = 2 + 4  / 2 => 6  / 2 = 3                  x" = 2 - 4  / 2 => - 2  / 2 = - 1